Spreadsheet model for MorphoSys RC array - Mansour, N. (2000)
This paper introduces reconfigurable computing and MorphoSys, which is a reconfigurable system. It also explains the architecture of its reconfigurable hardware part. Then, it presents two spreadsheet models for the operation of this reconfigurable device. The first spreadsheet performs the modelling through formulas, while the second does it numerically. These spreadsheet models serve as design and debugging tools.